Retos y desafíos del Trabajo Social en el sector rural: una mirada desde el emprendimiento social - Loor Tobar, Gloria Gema (2021)
The objective of this research was to describe the challenges that the Social Worker faces within his intervention in the field of social entrepreneurship in the rural sector. The methodological design used lays its foundations in a bibliographic review of different authors that support the importance of Social Work in the rural sector to face the challenges and structural challenges, then the descriptive research allowed to know the main obstacles and limitations of Social Work as tool to support agricultural associations. The research techniques are supported by a qualitative-quantitative analysis through a survey applied to 17 agro-entrepreneurs (6 women and 11 men aged 18 to 73 years) from the Association of Agricultural Production "Convento" and an interview conducted to the Social Worker, pioneer of the organization. Among the results obtained, it was evidenced that the main challenges of Social Work during the execution of an entrepreneurial project is the creation of sources of employment, the formation of a solid team and updating knowledge, in the same way, among the challenges revealed in the research are placing in the market, obtaining financing and disposing of capital. The results demonstrated the existence of challenges and challenges for the Social Work professional in the rural sector, which is why it is concluded that Social Work is a fundamental discipline that contributes to the design and management of sustainable projects, contributing to local development through social entrepreneurship.